Common Thinking Styles in the light of the Mental Self-Government Theory amongst Students at Jordanian Universities - Ferial Abu Awwad; Mohammad Nofal (My University, 2012)
This study aimed at investigating common thinking styles in the light of the theory of the mental self-government amongst students at Jordanian universities. To achieve this aim, the Thinking Styles Scale which was developed by Sternberg and Wagner, and its verified psychometric characteristics were used. The study sample consisted of (1174) students, of whom (402) from scientific faculties, and (772) from humanistic faculties. Results of the study showed the prevalence of the conservative style, the local style, and the monarchic, while the less common styles are: the legislative, the hierarchical, and the external. The study revealed that there were statistically significant differences between students’ means of scores on the judicial, monarchic, oligarchic and external styles attributed to gender in favor of the males on each of the judicial, oligarchic and external, and in favor of the females on the monarchic style. There were statistically significant differences between students’ means of scores on the judicial, local, progressive, hierarchical, and oligarchic thinking styles attributed to the students’ specialization in favor of students in scientific faculties in the oligarchic style, and for humanistic faculties in the other styles, and there was a weak positive correlation between the students’ GPA and some thinking styles. The study proposes some recommendations such as: developing the scale of Sternberg and Wagner on the Jordanian environment, and exploring its predictive value in light of different variables.

هدفت الدراسة الحالية إلى استقصاء أساليب التفكير الشائعة في ضوء نظرية حكومة الذات العقلية لدى طلبة الجامعات الأردنية، ولتحقيق أهداف الدراسة تم استخدام قائمة أساليب التفكير المطورة من قبل كل من ستيرنبيرغ وواجنر Sternberg & Wagner بصورتها المطولة بعد التأكد من خصائصها السيكومترية، وتكونت عينة الدراسة من 1174 طالباً وطالبة منهم 402 يمثلون الكليات العلمية، و772 يمثلون الكليات الإنسانية، وكان من أبرز نتائج الدراسة شيوع الأسلوب المحافظ، فالأسلوب المحلي، ثم الملكي، في حين كانت أقل الأساليب شيوعاً هي: الأسلوب التشريعي، فالهرمي، فالخارجي، وظهرت فروق دالة إحصائياً بين متوسطات درجات الطلبة على الأسلوب القضائي والملكي والأقلي والخارجي تعزى لمتغير الجنس، لصالح الذكور على كل من الأسلوب القضائي والأقلي والخارجي، ولصالح الإناث على الأسلوب الملكي، ووجدت فروق بين متوسطات درجات الطلبة على الأسلوب القضائي والمحلي والتقدمي والهرمي والأقلي تعزى لمتغير التخصص الدراسي، لصالح طلبة الكليات العلمية على الأسلوب الأقلي، ولصالح طلبة الكليات الإنسانية على الأساليب الأخرى، وظهرت علاقة ارتباطية ضعيفة بين المعدل التراكمي وبعض أساليب التفكير، وقد انتهت الدراسة بعدد من التوصيات أبرزها: تقنين مقياس أساليب التفكير لستيرنبيرغ وواجنر على البيئة الأردنية، واستقصاء القيمة التنبؤية لمقياس أساليب التفكير لستيرنبيرغ وواجنر مع متغيرات أخرى.
أساليب التفكير الشائعة في ضوء نظرية حكومة الذات العقلية لدى طلبة الجامعات الأردنية